Online/ICT based Education and COVID-19 Pandemic: Challenges for School Education in India - Yadav, Pushpendra; Ingole, Meenakshi (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
In the last two years, not only India but the entire world has witnessed the danger and consequences of the Covid-19 pandemic, surely it has come as the biggest pandemic of the century that shook the entire human race from within. This pandemic has affected all of us, due to which we have to make changes in our lifestyle. All educational institutions in India were closed from March 2020 to prevent the spread of the pandemic and all of a sudden we had to shift our education system completely to online mode because at that time to prevent the spread of the pandemic and help the students. There was no better option than this to continue studies. India is a developing country and here the necessary infrastructure for online/ICT based education, trained teachers and policy for online education was in a development order. Therefore, due to the pandemic, due to the shift of the entire education system towards online and ICT based education, it has emerged with many challenges for the students, teachers, school leaders, parents and policy makers. In this review based article, the researcher has tried to analyze the challenges faced by stakeholders especially in school education during Covid-19.